Cholesterol and triglycerides as biochemical markers of the state of the patient’s illness with acute lymphocytic leukemia - GUZMÁN, MARCO (2004)
Objective: To determine the relationship of cholesterol and triglycerides serum levels with the response to induction chemotherapy treatment in patients with acute lymphocytic leukemia. Material and Methods: The sample consisted in 25 patients 2 through 18 years-old admitted to the Neoplasia Diseases Institute with a recent diagnosis of acute lymphocytic leukemia in whom serum concentrations of total cholesterol, HDL-cholesterol, LDL-cholesterol and triglycerides were determine, before and after the first phase of the induction chemotherapy. Results: Only 23 patients responded to the treatment and in them we observe an increment from 19,24 ± 4,49 mg/dL to 46,84 ± 15,38 mg/dL for the HDL-cholesterol, and a descent from 153,66 ± 36,39 mg/dL to 79,79 ± 34,53 mg/dL for the triglycerides (p<0,0001). On the contrary, in the patients that didn’t respond to the treatment, an increment was obtained from 14,64 ± 2,46 mg/ dL to 23,13 ± 14,23 mg/dL for HDL-cholesterol and an increment from 121,88 ± 0,56 mg/dL to 161,01 ± 75,25 mg/dL for triglycerides. Conclusion: Serum concentrations of cholesterol and triglycerides are correlated with the state of the patient’s illness with acute lymphocytic leukemia. We propose these metabolites as biochemical markers in the clinical pursuit of this illness.